Antioxidant Enzyme Inhibitor Role of Phosphine Metal Complexes in Lung and Leukemia Cell Lines - Burcu Saygıdeğer Demir; Tuğba Keleş; Osman Serindağ (Bioinorganic Chemistry and Applications)
Phosphine metal complexes have been recently evaluated in the field of cancer therapy. In this research, the cytotoxic effects of some metal phosphines {[PdCl2((CH2OH)2PCH2)2NCH3] (C1), [RuCl2(((CH2OH)2PCH2)2NCH3)2] (C2), [PtCl2((Ph2PCH2)2NCH3)(timin)2] (C3)} on K562 (human myelogenous leukemia cell line) and A549 (adenocarcinomic human alveolar basal epithelial cells) cells were investigated using the MTT test. C1 and C2 are water-soluble metal complexes, which may have some advantages in in vitro and in vivo studies. The effects of the above-mentioned metal complexes on thioredoxin reductase (TrxR) (EC: 1.8.1.9), glutathione peroxidase (GPx) (EC: 1.11.1.9), and catalase (Cat) (EC: 1.11.1.6) enzymes were also tested. The results of this research showed that all three metal complexes indicated dose-dependent cytotoxicity on A549 and K562 cell lines and that the complexes inhibited different percentages of the TrxR, GPx, and Cat enzymes of these tumor cells.